Evaluasi Kinerja Fisik Bangunan Irigasi Berdasarkan Indeks Kinerja pada Daerah Irigasi Gesang, Kecamatan Ngajum - Puguh Dedy Prasetya; Yurnalisdel Yurnalisdel; Handika Setya Wijaya (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
A decline in irrigation system performance is generally caused by infrastructure degradation and suboptimal management, which affect the effectiveness of water distribution to agricultural land. This study aims to evaluate the physical and functional performance of the irrigation network in the Gesang Irrigation District in Malang Regency as a basis for determining appropriate maintenance strategies. The research method employed a field survey approach and an irrigation performance index assessment based on parameters including physical infrastructure, crop productivity, supporting facilities, personnel organization, documentation, and the institutional framework of water-user farmers. The assessment was conducted on 33 sections of primary canals through observation of structural conditions and calculation of performance weights. The results of the study indicate that the physical condition of the infrastructure exhibits varying degrees of damage, with the following proportions: Good at 33.33%, Slightly Damaged at 33.33%, Moderately Damaged at 21.21%, Severely Damaged at 9.09%, and Natural at 3.03%. The overall performance score for the physical infrastructure reached 73.16%, which falls into the Moderately Damaged category. The component with the lowest score was the control structures at 67.50%, due to malfunctions in the distribution gates and intake structures. These conditions indicate that water distribution functions are beginning to be disrupted, necessitating rehabilitation at points of severe damage as well as intensive preventive maintenance to ensure the sustainability of irrigation services.